Picturing Life - Molly Bathje MS, OTR/L (Scholarworks @ WMU, 2013)
The cover art of the summer 2013 issue of The Open Journal of Occupational Therapy provided by Jonathan Darnall reflects his unique life perspective, current roles, and values. An exploration of Jon's life experience reveals how creative arts, including photography, have positively influenced his life and inform OT practitioners about the benefits of photography as an intervention and an occupation.